Eksperimentasi Model Numbered Heads Together (NHT) danTeams games tournament (tgt) terhadap hasil belajarMatematika ditinjau dari Kemampuan Awal Pada SiswaKelas Vii Smp Negeri 2 Colomadu Tahun Ajaran 2015/2016 - Sholikhah, Farida Umi (2016)
The purpose of the research are to analyze: (1) effects of learning models Numbered Heads Together and Teams Games Tournament in mathematics learning outcomes (2) effects prior knowledge direct learning in mathematics learning outcomes (3) interaction learning models Numbered Heads Together and Teams Games Tournament in terms of prior knowledge direct learning in mathematics learning outcomes. The research use quasi experimental metohod with design factorial 2x3. The sample of research taken using the cluster random sampling from population all of the class VII student at SMP Negeri 2 Colomadu regency academic year 2015/2016. The test instrument achievement test includes validation and reliability .Technique of collecting data use documentation and the result of the study. Before to the analysis, first test consist of normality test and Homogeneity test. The hypotesistest used unbalance two way analysis of variance with α = 5%. From the analysis, it is found that : (1)there was an effects models Numbered Heads Together and Teams Games Tournament in mathematics learning outcomes (2) there was not effects prior knowledge direct learning in mathematics learning outcomes (3)there was not interaction learning models Numbered Heads Together and Teams Games Tournament in terms of prior knowledge direct learning in mathematics learning outcomes.